1999
DOI: 10.1007/s001090050319
|View full text |Cite
|
Sign up to set email alerts
|

Critical islet mass for successful porcine islet autotrasplantation

Abstract: A major reason for the failure of clinical islet transplantations may be a limited islet mass. The aim of this study was to determine the critical islet mass necessary for normalization of glucose metabolism in a porcine model. Diabetes was induced by total pancreatectomy. The splenic lobe of the pancreas was intraductally distended with UW-solution containing 2.67-3.33 mg/ml collagenase, and the distended pancreas was digested in a continuous digestion filtration device. The islets were purified on a isoosmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…These drawbacks indicated that transplantation of a sufficient number of islets, ϳ6,000 islet equivalents/kg body wt (1 islet equivalent ϭ 150-m diameter islet), is an essential condition for a successful graft (49). The high level of ␤-cell loss subsequent to isolation makes this number of islets difficult to obtain from one single pancreas, making until recently the use of "double-donor" transplants to provide for an adequate therapeutic islet mass a prerequisite to successful grafting (50). Better pancreas preservation before islet transplantation remains therefore one of the potential improvements to overcome islet shortage and to improve PNF (46,51).…”
Section: Discussionmentioning
confidence: 99%
“…These drawbacks indicated that transplantation of a sufficient number of islets, ϳ6,000 islet equivalents/kg body wt (1 islet equivalent ϭ 150-m diameter islet), is an essential condition for a successful graft (49). The high level of ␤-cell loss subsequent to isolation makes this number of islets difficult to obtain from one single pancreas, making until recently the use of "double-donor" transplants to provide for an adequate therapeutic islet mass a prerequisite to successful grafting (50). Better pancreas preservation before islet transplantation remains therefore one of the potential improvements to overcome islet shortage and to improve PNF (46,51).…”
Section: Discussionmentioning
confidence: 99%
“…However, most likely, the different results obtained are, to some extent, explained by the relatively small number of observations in each study and the possibility that variability in ␤-cell function at very low values of ␤-cell mass seems to occur. Transplantation studies in both humans (16) and pigs (17) have shown a strong relation between islet mass and metabolic control. Since the ␤-cell mass (milligrams per kilogram body weight) in pigs is higher than in humans, this could affect the way in which functional tests can be used as a predictor of ␤-cell mass in each species.…”
Section: Discussionmentioning
confidence: 99%
“…In animals dosed with NIA plus STZ or STZ alone, pancreata were obtained 35 Ϯ 27 days (range 11-84) after the OGTT and 8 Ϯ 7 days (range 0 -27) after the insulin secretion test. In the normal control animals, pancreata were obtained 21 Ϯ 4 days (range [17][18][19][20][21][22][23][24][25][26] after the OGTT and 13 Ϯ 7 days (range 6 -23) after the insulin secretion test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both effects, stress conditions during isolation and nonspecific inflammatory events following transplantation, then combine to strongly impair viability of islets. Consequently, a high number of islets from multiple donors are required to perform islet grafting [9], and therefore islet shortage and early loss of FIM are the main limitations to the expansion of islet transplantation as a curative therapy for type 1 diabetes mellitus [10].…”
Section: Introductionmentioning
confidence: 99%